The feasibility of using an electronic nose to identify adulteration of Pathumthani 1 in Khaw Dok Mali 105 rice during storage - Udomkun, Patchimaporn; Innawong, B.; Niruntasuk, K. (Springer, 2018)
This study aimed to classify the degree of adulteration of Pathumthani 1 in Khaw Dok Mali (KDML) 105 rice during up to 5 months’ storage. KDML 105 was mixed with Pathumthani 1 at seven different ratios (100:0, 95:5, 92:8, 90:10, 85:15, 80:20, and 0:100, w/w). The electronic nose (E-nose) was used to investigate the changes of aroma profiles in mixed rice, while GC–MS was conducted to determine the volatile compounds of each variety. The quantity of 2-acetyl-1-pyrroline (2-AP) was found to notably decrease to 42.1 and 48.7%, respectively, while hexanal increased by 20.3 and 26.6%, respectively, during 5 months of storage. The E-nose potentially exhibited the ability to discriminate the aroma profiles of two rice varieties at the ratio 100:0 and 0:100 during storage. However, the aroma profiles of mixed rice during storage were not clearly separated due to the alteration of volatile compounds in rice.